2022
DOI: 10.1002/lno.12235
|View full text |Cite
|
Sign up to set email alerts
|

Interactive effects of temperature and nitrogen source on the elemental stoichiometry of a polar diatom

Abstract: Author Contribution Statement: N.S. designed the experiments, grew the cultures and conducted the analyses. N.S. and J.-E.T. wrote the manuscript with feedback from M.B.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 58 publications
(97 reference statements)
1
1
0
Order By: Relevance
“…Consistently, a study on polar diatoms found that temperatures above 6 °C tend to be supra-optimal for them [ 82 ]. Similar results were found for an Arctic Chaetoceros strain [ 83 ]. However, the intra-specific variation approaching the thermal limits of diatoms appears to be high [ 82 , 84 ], and therefore polar species might adapt to warming in the longer term.…”
Section: Discussionsupporting
confidence: 87%
“…Consistently, a study on polar diatoms found that temperatures above 6 °C tend to be supra-optimal for them [ 82 ]. Similar results were found for an Arctic Chaetoceros strain [ 83 ]. However, the intra-specific variation approaching the thermal limits of diatoms appears to be high [ 82 , 84 ], and therefore polar species might adapt to warming in the longer term.…”
Section: Discussionsupporting
confidence: 87%
“…The Rubisco percentages of total protein we measured in Jones Sound could be driven lower by higher contributions of heterotrophic microbial biomass compared to the intense phytoplankton bloom conditions examined in the Southern Ocean by Young et al (2015 a , b ). Similarly, recent studies of a specific Arctic Chaetoceros species, Chaetoceros gelidus , show evidence of the widespread diatom species exhibiting growth rates more similar to temperate phytoplankton species (Schiffrine et al 2022). It is also important to note that all previous data used to calculate % Rubisco were generated using western blots rather than quantitative mass spectrometry.…”
Section: Discussionmentioning
confidence: 79%